Tanker spills : prevention by design (National Academy Press, 1991)
"Can we design an oil tanker that meets our complex demands for environmental protection, economical operation, and crew safety? This volume evaluates and ranks a wide variety of tank ship hull designs proposed by experts around the world. Based on extensive research and studies, the book explores the implications of our rising demand for petroleum and increase in tanker operations; U.S. government regulations and U.S. Coast Guard policies regarding designs for new tank vessel construction; how new ship design would affect crew safety, maintenance, inspection, and other technical issues; the prospects for retrofitting existing tankers to reduce the risk of oil spills; and more. The conclusions and recommendations will be particularly important to maritime safety regulators in the United States and abroad; naval architects; ship operators and engineers; and officials in the petroleum, shipping, and marine insurance industries."